Realisme Sosial dalam Puisi سفر الخروج من ايرلندا karya Marwan Makhoul: Analisis Strata Norma - Agustin, Hesti (Lingua Susastra, 2024)
The purpose of this study is to analyze social realism in the poem Sifru Al-Khuruji min Irlanda by Marwan Makhoul using Roman Ingarden's norm strata theory. This research is motivated by the desire to explore how Makhoul uses his poetry as a medium to voice social reality, politics, and Palestinian identity. The method used is qualitative-descriptive. The poem Sifru Al-Khuruji min Irlanda served as primary data, while relevant books and journals served as secondary data. The results show that the poem embodies the school of social realism that describes the situation and conflict in Palestine. The analysis also shows that the poem contains layers of meaning in accordance with Roman Ingarden's theory of normative strata. In conclusion, Sifru Al-Khuruji min Irlanda has a deeply layered structure of meaning, ranging from the phonetic layer to the metaphysical layer, which enriches its message and aesthetic value. It effectively communicates Palestinian identity and struggle, and makes a significant contribution in the context of contemporary Arabic literature.